Development of a conceptual framework of childhood tuberculosis within which to study the impact of a preventive therapy program for childhood tuberculosis prevention in high burden communities - Mandalakas, Anna Maria (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.